Coatings and Thin-Film Technologies 2019
DOI: 10.5772/intechopen.79747
|View full text |Cite
|
Sign up to set email alerts
|

Ti-Al-N-Based Hard Coatings: Thermodynamical Background, CVD Deposition, and Properties. A Review

Abstract: For several decades, the increasing productivity in many industrial domains has led to a significant and ever-increased interest to protective and hard coatings. In this context, titanium-aluminum nitrides were developed and are now widely used in a large range of applications, due to their high hardness, good thermal stability, and oxidation resistance. This chapter reviews the thermodynamical characteristics of the Ti-Al-N system by reporting the progress made in the description of the Ti-Al-N phase diagram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…The range of 13.5–19.7 GPa in this study confirms very good hardness of the bulk TiN nanoceramics. The remarkably high hardness of the metastable cubic Ti 1−x Al x N was mentioned earlier [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Although Ti 1–x A x N is not encountered in our ceramics, it is worth quoting its indentation hardness of 24–37 GPa, which is markedly decreased at high temperatures [ 65 ].…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The range of 13.5–19.7 GPa in this study confirms very good hardness of the bulk TiN nanoceramics. The remarkably high hardness of the metastable cubic Ti 1−x Al x N was mentioned earlier [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Although Ti 1–x A x N is not encountered in our ceramics, it is worth quoting its indentation hardness of 24–37 GPa, which is markedly decreased at high temperatures [ 65 ].…”
Section: Resultsmentioning
confidence: 66%
“…This has to be confronted with the established, for nearly three decades, various technologies for large scale preparations of the very hard and oxidation resistant coatings described as made of cubic Ti 1−x Al x N, i.e., a structure formed by substituting some titanium centers with aluminum ones in the reference cubic titanium nitride. Such a metastable phase has been prepared mostly in the form of thin films via various gas phase deposition techniques at relatively high temperatures to wide utilization at ambient to mild conditions [ 31 , 32 , 33 , 34 ]; these films decompose to the stable polytypes of h-AlN and c-TiN at suitably high temperatures in the order of 800–1000 °C and higher [ 35 , 36 ]. In rare cases, the “phase of Ti 1−x Al x N” has appeared up-front to be an intimate mixture of c-TiN and amorphous AlN domains [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous experimental reports indicated a complex correlation between the applied deposition conditions, the nanolamellar microstructure and the functional properties of the self-assembled nanolamellar CVD Al x Ti 1−x N coatings. As indicated especially in the latter three of the abovementioned studies [18][19][20], significant differences in nano-lamellar morphology, thickness, chemistry, and phase composition have been observed and correlated especially with the precursor gases' flow, pressure, and ratio. Although the role of the applied precursor atmosphere has been evaluated extensively, the effect of other deposition parameters in the formation of the unique self-assembled microstructure remains largely unexplored.…”
Section: Introductionmentioning
confidence: 83%
“…More recently, Ishigaki et al [18] correlated the thickness of the nanolamellae with the Al content in the deposited Al x Ti 1−x N coatings and indicated that the coatings with the highest Al content exhibited the most promising mechanical properties. Similarly, Uny et al [19] studied self-assembled Al x Ti 1−x N CVD coatings deposited at a relatively high working pressure of 4 kPa and low carrier gas flow. These exhibited less pronounced nanolamellar microstructures resulting in lower hardness compared to the aforementioned results.…”
Section: Introductionmentioning
confidence: 99%